The cyberpolitical space of the European Union: an overview of e-Government, e-Democracy and interoperability in the European space and its citizenship - Vieira, Rui Castro (2018)
e-Government and e-Democracy, in the latest decades, with the recent fast-paced developments of information and communication technologies, have been regarded as new mechanisms to enrich the democratic culture and link institutions to its citizens. The European Union is a peculiar case with its own idiosyncratic form of citizenship. In this paper, we analyse the progresses of e-Democracy in the European Union and its developments through interoperability projects, as well as its challenges with the uprising, in the latest years, of many problems that came from the use of these technologies. We argue that a promotion of the European citizenship is necessary in the development of a European Union cyberspace.